Insight into the physiological and molecular response of low light stress tolerance in rice - Haque, M A; Sen, A; Akter, S E; Khan, N A; Rahman, M A; Tuhin, K B M O F (Bangladesh Journal of Nuclear Agriculture, 2025)
Rice is a sensitive crop, and its growth is highly affected by abiotic stresses. Among the abiotic stresses, low light intensity is one of the most critical environmental elements influencing plant growth and development. It regulates plants development and production by determining photosynthetic rate and accumulative assimilation. Plants, on the other hand, are often exposed to excessive or insufficient light intensities, and such variations, commonly referred to as light stress, have an impact on their agronomic traits by restricting physiological metabolic processes such as photosynthesis, antioxidant machinery, and their ability to fix atmospheric carbon and nitrogen. Photosystem II (PSII) and its reaction centres are particularly vulnerable to these disturbances and have thus been identified as main targets of light stress at the physiological, biochemical, and molecular levels. This paper reviews the response of low light levels on rice productivity and quality from morphological, physiological, biochemical, and molecular perspectives. We have attempted to present the advancements of molecular studies in this crucial field of low-light stress tolerance in rice. We also summarised the need for future research, emphasising the need for techniques that can effectively increase rice grain yield and quality in low-light conditions. Bangladesh J. Nuclear Agric, 38(2): 49-63, 2024